Analisis Rasionalisasi Jaringan Pos Hujan Untuk Kalibrasi Hidrograf Pada Das Babak Kabupaten Lombok Tengah - Ranesa, Lalu Sigar Canggih; Limantara, Lily Montarcih; Harisuseno, Donny (Fakultas Teknik, Universitas Brawijaya, 2015)
Babak watershed is one of the major watersheds in Lombok with Â± 259.166 km watershed area. Babak watershed is affected by 6 rainfall stations spread inside and outside the watershed. By using the standard of WMO (World Meteorological Organization) for mountainous area with the range of 100-250 km 2 /station for the tropics, assessment and analysis have been made and shown that two stations which did not fit the WMO standards of rain heading density. For example Keru and Jurang Sate Rainfall station, each of the station has an area of influence Â± 60 km 2 . Furthermore, from the assessment and analysis using Kagan-Rodda method, there were two selected stations. While using Kriging method, there were three stations that have been chosen with one new placement inside the Babak watershed. Relative error of design rainfall for Kagan-Rodda method was between 2.36% -18.60% for every return period; whilst for Kriging method was between 7.90% - 13.57%. Hydrograph calibration result of Collins observation unit and Nakayasu synthetic unit rendered in Î± value of 1.27 for Babak watershed; relative error for Nakayasu design flood of Kagan-Rodda method for every return period was between 0.35% -18.21% while Kriging method was between 8.90% - 13.04%.Key Word : Rainfall stasiun,, Rationalization, WMO, Kagan-Rodda, Kriging, Collins.